Microbes and metabolites of a plant-parasite interaction: Deciphering the ecology of Tetrastigma host choice in the world’s largest parasitic flower, Rafflesia - Jeanmaire Molina; Roche C. de Guzman; Rinat Abzalimov; Wenkai Huang; Anusha Guruprasad; Ronniel Pedales; Adhityo Wicaksono; Destiny Davis; John Rey Callado; Hans Bänziger; Piyakaset Suksathan; William Eaton; et al. (Current Plant Biology)
Rafflesia, known for producing the world’s largest flowers, is a holoparasite found only in Southeast Asia's rapidly diminishing tropical forests. Completely dependent on its Tetrastigma host plants, Rafflesia grows covertly within its host until flowering, but the ecological factors driving host susceptibility are unknown. With most Rafflesia species on the brink of extinction due to habitat loss, understanding the complex ecological interactions between Rafflesia and its host is crucial for conservation. In this study, we integrated metagenomic data with metabolomic profiles to identify potential functional relationships between microbial communities and specific metabolites, shedding light on their ecological roles in Rafflesia's life cycle. Key findings reveal that microbial taxa such as Microbacteriaceae and Nocardioidaceae correlate with elevated levels of polyphenols, particularly gallic acid derivatives, which may shape the chemical environment conducive to Rafflesia development. Complex-carbon-degrading bacteria thrive in the chemically distinct environment of Rafflesia buds, while an unknown group of Saccharimonadales was enriched in Tetrastigma host species. Docosenamide production in Rafflesia buds and their hosts may facilitate parasitic infection, while coumarin compounds in non-host Tetrastigma species may exert allelopathic effects. The enrichment of gallic acid derivatives, the phytohormone adenine, and gall-associated bacteria suggests that Rafflesia buds may function similarly to plant galls, manipulating host tissues to support their reproductive development. This study highlights the dynamic microbial shifts during Rafflesia’s development, emphasizing its symbiotic relationship with microbial communities and hosts. In identifying essential microbial and chemical conditions that could improve propagation techniques, this research has practical applications in ex situ conservation efforts, aiding in the rescue of the world’s largest flowers from the brink of extinction.